Envelope of Collapse in Gypseous Sandy Soils using Finite Element Method and Particle Image Velocimetry - Hala Mahmood Jawad; Zuhair Kadhim Jahanger (Journal of Engineering)
Water level rise as well as inundation to gypseous soil medium can lead to a substantial loss of volume of the soil, with or without adding load. Macromechanical behavior of gypseous sandy soils using particle image velocimetry (PIV) is yet to be studied, with a particular emphasis on patterns of collapse. These unique patterns have given attention to researchers on deformable soils, but the difficulties of gypseous sandy soil still need to be addressed. Consequently, this study aims to quantify the local-scale displacement fields and patterns of failure of gypseous sand interacting with rigid strip foundations under static stress under comparison, emphasizing wetting due to rising the water table and the dry state using an experimental model and finite element method (FEM). The PIV results showed that the pattern of collapse of the gypseous sandy soil is of the type of punching shear failure, which validated the FEM and these patterns related to soil vertical deformation. Where FEM and PIV results were corresponded well. In addition, the built soil models in FEM are essentially oversimplified representations of the real behavior of the foundation. The outcomes reveal that local scale failure patterns of gypseous soil medium are essential for improving the design of foundations.